EMOTIONAL PERCEPTION DISTURBANCES IN ANOREXIA NERVOSA - Aleksandra Nowińska; Monika Grudzień; Anna Gryc; Jakub Lipiec; Marcin Narloch; Aleksandra Gradek; Mateusz Raniewicz; Aleksandra Skorupa; Paulina Pawłowska; Marta Steuden (International Journal of Innovative Technologies in Social Science, 2025)
Anorexia nervosa (AN) is a severe and debilitating disorder with the highest standardized mortality rate among all mental health conditions. It is associated with cognitive impairments and difficulties in emotional regulation. Individuals with AN often exhibit a reduced ability to recognize emotions (Emotion Recognition Ability – ERA), particularly when it comes to negative emotions. The efficiency of emotion recognition has been found to correlate with Body Mass Index (BMI) and the duration of the illness, which may suggest a decline in socio-emotional functioning and neurobiological changes caused by prolonged starvation. Impaired emotion recognition is linked to poorer treatment outcomes, making it crucial to focus on enhancing this skill during AN therapy. Since ERA plays a fundamental role in nonverbal communication – and, by extension, in social interactions – further research in this area is warranted. Available training programs aimed at improving emotion recognition abilities have the potential to significantly enhance communication between patients and healthcare providers as well as close relatives, thereby positively influencing the therapeutic process.